Dipeptidyl Peptidase IV Inhibition Exerts Renoprotective Effects in Rats with Established Heart Failure - Arruda-Junior, Daniel F.; Martins, Flavia L.; Dariolli, Rafael; Jensen, Leonardo; Antonio, Ednei L.; dos Santos, Leonardo; Tucci, Paulo J. F.; Girardi, Adriana C. C. (Frontiers in Physiology, 2016)
Circulating dipeptidyl peptidase IV (DPPIV) activity is associated with worse cardiovascular outcomes in humans and experimental heart failure (HF) models, suggesting that DPPIV may play a role in the pathophysiology of this syndrome. Renal dysfunction is one of the key features of HF, but it remains to be determined whether DPPIV inhibitors are capable of improving cardiorenal function after the onset of HF. Therefore, the present study aimed to test the hypothesis that DPPIV inhibition by vildagliptin improves renal water and salt handling and exerts anti-proteinuric effects in rats with established HF. To this end, male Wistar rats were subjected to left ventricle (LV) radiofrequency ablation or sham operation. Six weeks after surgery, radiofrequency-ablated rats who developed HF were randomly divided into two groups and treated for four weeks with vildagliptin (120 mg/kg/day) or vehicle by oral gavage. Echocardiography was performed before (pretreatment) and at the end of treatment (post-treatment) to evaluate cardiac function. The fractional area change increased (34±5 vs. 45±3%, p<0.05), and the isovolumic relaxation time decreased (33±2 vs. 27±1 ms; p<0.05) in HF rats treated with vildagliptin (post-treatment vs. pretreatment). On the other hand, cardiac dysfunction deteriorated further in vehicle-treated HF rats. Renal function was impaired in vehicle-treated HF rats as evidenced by fluid retention, low glomerular filtration rate (GFR) and high levels of urinary protein excretion. Vildagliptin treatment restored urinary flow, GFR, urinary sodium and urinary protein excretion to sham levels. Restoration of renal function in HF rats by DPPIV inhibition was associated with increased active glucagon-like peptide-1 (GLP-1) serum concentration, reduced DPPIV activity and increased activity of protein kinase A in the renal cortex. Furthermore, the anti-proteinuric effect of vildagliptin treatment in rats with established HF was associated with upregulation of the apical proximal tubule endocytic receptor megalin and of the podocyte main slit diaphragm proteins nephrin and podocin. Collectively, these findings demonstrate that DPPIV inhibition exerts renoprotective effects and ameliorates cardiorenal function in rats with established HF. Long-term studies with DPPIV inhibitors are needed to ascertain whether these effects ultimately translate into improved clinical outcomes.